Cubism and abstract art : painting, sculpture, constructions, photography, architecture, industrial art, theatre, films, posters, typography /: painting, sculpture, constructions, photography, architecture, industrial art, theatre, films, posters, typography. (2018) - Jr, Barr, Alfred H, 1902-1981
No abstract available